برصغیر میں سب سے پہلا مکمل منظوم ترجمۂ قرآن تعارف و تجزیہ --------------------------------------------------------------------------------- An Introductory and Critical Analysis of the First Versified Translation of the Holy Quran in the Sub Continent - شیخ, محمد سعید (FIKR-O NAZAR فکر ونظر, 2016)
The scholars of every era have translated the Holy Qur’an into various languages but the Urdu language enjoys a notable position in this regard. A distinctive feature of this corpus is the versified translations. Approximately nineteen complete versified translations have been published in addition to partial translations. The translation of the Quran in prose is a very difficult task because of its sublime eloquence and literary nuances. This difficulty multiplies in case of the versified translation due to strict conditions of verse. The writer has chosen a translation named Nazm al-Bayan out of the poetical translations of the Quran, by a comparatively anonymous author Shamsudd┘n Shaiq Iizdi. It is the first complete versified translation of the Holy Quran in Urdu language. The writer has introduced the translator in addition to the characteristics of this versified rendering of the Quran. Secondly, the translation has been critically examined and its merits and demerits have been allaboraated.